Getting real about China: myths about China debunked - Blankert, Jan Willem (Henry Stewart Talks, 2014)
Myths about China, The serious problem in China's rise, China's perspectives, Myth 1: "when China rules the world", Myth 2: "They are stealing our jobs", Myth 3: "China will overtake us", Climbing the world prosperity ladder, Myth 4: “China is buying up the world”, Myth 5: “China will never be a democracy”, China in the East Asia region, China and ASEAN, China relations with Taiwan and Japan